Development and Evaluation of a Sustainable e-Learning Framework for Higher Education Institutions in Malaysia - Mohamed Sofiadin, Aidrina binti (Curtin University, 2018)
This thesis focuses on developing and evaluating a sustainable e-learning framework (SeLF) for the higher education institutions in Malaysia. A mixed methods approach was used. Data was collected through surveys from Malaysian universities to assess the characteristics of SeLF. The framework was then evaluated through expert interviews. The thesis highlights SeLF elements and their contribution to the Triple Bottom Line, facilitating sustainable e-learning and its contribution to society, the environment, and the economy.